Feminism in Public Debt: A Human Rights Approach - Juan Pablo Bohoslavsky; Mariana Rulli (Bristol University Press, 2024)
EPDF and EPUB available open access under CC-BY-NC-ND licence. As many developing countries are facing increasingly higher levels of debt and economic instability, this interdisciplinary volume explores the intersection of sovereign debt and women's human rights. Through contributions from leading voices in academia, civil society, international organizations and national governments, it shows how debt-related economic policies are widening gender inequalities and argues for a systematic feminist approach to debt issues. Offering a new perspective on the global debt crisis, this is an invaluable resource for readers who seek to understand the complex relationship between economics and gender.
Keywords: 320; Human rights; International financial institutions; Neoliberalism; Sovereign debt; Women